2012
DOI: 10.1128/cvi.05642-11
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T Cell Antigens from Staphylococcus aureus Newman Strain Identified following Immunization with Heat-Killed Bacteria

Abstract: ABSTRACTStaphylococcus aureusis a commensal bacterium associated with the skin and mucosal surfaces of humans and animals that can also cause chronic infection. The emergence of antibiotic-resistant strains such as methicillin-resistantS. aureus(MRSA) and strains causing chronic intramammary infections (IMI) in cows results in severe human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 95 publications
0
21
0
Order By: Relevance
“…Hence, BME extract comprising most exoproteins of the biofilm matrix may ensure that not only different areas of the biofilm but also various cell types present within the biofilm are targeted. It is important to note that vaccinations with other multicomponent extracts, such as a heat-killed or a PLKE, which have been shown to provide protection against S. aureus infections (41,61,62), were less efficient than BME in reducing the number of bacteria inside a biofilm, using a mesh-associated biofilm infection model. The reason behind the low efficiency of heat-killed and PLKEs might be that they probably do not include biofilm-specific antigens like the BME extract (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, BME extract comprising most exoproteins of the biofilm matrix may ensure that not only different areas of the biofilm but also various cell types present within the biofilm are targeted. It is important to note that vaccinations with other multicomponent extracts, such as a heat-killed or a PLKE, which have been shown to provide protection against S. aureus infections (41,61,62), were less efficient than BME in reducing the number of bacteria inside a biofilm, using a mesh-associated biofilm infection model. The reason behind the low efficiency of heat-killed and PLKEs might be that they probably do not include biofilm-specific antigens like the BME extract (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the numbers of CD4 ϩ and CD8 ϩ T cells did not differ significantly between groups B and D or between groups C and D. In general, CD4 ϩ (Th1 and Th2) T-helper cells activate opsonic IgG antibodies and cell-mediated immune responses, and cytotoxic CD8 ϩ T cells destroy the intracellular bacterial pathogens (36,37). It has previously been suggested that CD4 ϩ T cells are essential for the S. aureus vaccine to be effective (38). Moreover, the S. aureus envelope component of PA-immunized animals elicited higher levels of CD4 ϩ and CD8 ϩ T cells than that of control animals (39).…”
Section: Resultsmentioning
confidence: 93%
“…The same thing was reported by Rolph and Kaufmann (2001), Chen et al (2001) and Field et al (2007) which uses a combination of CD40 and vaccine of heat-killed Listeria mononcytogenes and Leishmania major. The development of vaccines based on cell-mediated immunity was also reported by Lawrence et al (2012) in a vaccination using HKSA. It was able to induce cellular immunity, particularly CD4+ T lymphocytes induced by superantigens found in isolates of S. aureus (strain Newman).…”
Section: Vaccination Based On Cell-mediated Immunitymentioning
confidence: 78%
“…While the role and ability of the neutrophils is enhanced by antibodies to kill S. aureus, the antibody alone without the action of the neutrophils, is known to be insufficient to provide protective effects (Jansen et al, 2013). In addition, several studies have developed a vaccine for S. aureus which is able to induce CD8+T cell (Rolph and Kaufmann, 2001) and CD4+ (Lawrence et al, 2012) as the main axis in cellular immunity.…”
Section: Vaccination Based On Cell-mediated Immunitymentioning
confidence: 99%
See 1 more Smart Citation